Individual approach to the research of mental and physical criteria of the oarsmen mastery on kayaks and canoe - Zharmenov, D.; Grenaderova, M. (Journal of Physical Education and Sport, 2018)
This article considers an individual approach to the study of the mental and physical criteria of oarsman skill. The solution to the problems of rowing development is possible only with a comprehensive study and the ability to control rowers with the help of psychological processes during their preparation and performances at competitions. The main idea of the research is aimed at an individual approach of studying the rowers mastery criteria. The study identified apparent influence effectiveness of the oarsman prelaunch status on his performances at the competitions. Our chosen direction to optimize the training process on canoe and kayak in combination with the objective quantitative characteristics of its health-improving efficiency is today quite promising for further improvement of athletes' performance at competitions. Rowers, who have high rates of mental and physical fitness, perform the application results and set records.